Identifikasi Bakteri Escherichia coli pada Sumur Gali Warga Dusun Penemung Kabupaten Sumbawa dalam Penyusunan Buku Petunjuk Praktikum Mikrobiologi - Layyina Annisa Syafar; Sri Nopita Primawati; Husnul Jannah (Biocaster : Jurnal Kajian Biologi, 2026)
Dug well water remains a primary source for meeting the daily water needs of many communities. However, the quality of dug well water can be influenced by environmental sanitation conditions, creating a potential risk of contamination by fecal indicator bacteria such as Escherichia coli. This study aimed to identify the presence of Escherichia coli in dug well water used by residents of Penemung Hamlet, Simu Village, Sumbawa Regency, and to develop and validate a research-based microbiology laboratory manual. An exploratory descriptive method was employed, involving sampling from ten dug wells. Bacterial isolation was performed using Eosin Methylene Blue Agar (EMBA) medium, followed by colony morphology identification, Gram staining, and IMViC biochemical testing. The laboratory manual was developed using the 4D model (up to the "develop" stage) and validated by media, language, and subject matter experts using Aiken's V index. The results showed that Escherichia coli was not detected in any of the samples using the employed methods. Based on morphological characteristics, Gram staining, and IMViC reaction patterns, the isolates were presumptively identified as Salmonella sp., Pseudomonas aeruginosa, and Citrobacter freundii. These identifications remain presumptive, as they have not yet been confirmed via molecular methods or automated bacterial identification systems. Validation results for the laboratory manual yielded Aiken's V scores of 0.86 for the media aspect (highly valid), 0.86 for the language aspect (highly valid), and 0.56 for the content aspect (valid). Consequently, the developed laboratory manual is deemed suitable for use as a supplementary resource for microbiology practical learning.